2010
DOI: 10.1007/s10804-010-9107-6
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Knowledge as a Compensation Determinant of Adult Age Differences in Verbal Fluency Tasks over Time

Abstract: The aim of this study was to determine whether verbal knowledge can compensate for the age-related decline in word production during a fluency test. We assessed the performance of 20 young and 20 old subjects in standard letter and semantic fluency tasks over time (T1: 0-30 s vs. T2: 31-60 s). The number of words produced, switching, and clustering components (Troyer et al. Neuropsychology, 11(1): 138-146, 1997) were investigated. Correlations between age and cognitive factors (processing speed, executive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 52 publications
3
52
0
1
Order By: Relevance
“…It should be noted that the level of performance of elderly age groups with a mean age greater than 75 years rapidly decreased. 2,11 Based on these results, we suggest that age-related cognitive decline could be described by the functional changes observed in the present study. The present findings were in line with those of previous studies, suggesting that the name generation function declines with aging.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It should be noted that the level of performance of elderly age groups with a mean age greater than 75 years rapidly decreased. 2,11 Based on these results, we suggest that age-related cognitive decline could be described by the functional changes observed in the present study. The present findings were in line with those of previous studies, suggesting that the name generation function declines with aging.…”
Section: Discussionsupporting
confidence: 78%
“…15 Because of the degeneration of the brain during aging, older adults in the present study were expected to show a decline in performance in the SVF task. 2 The present study is noteworthy, because it is the first attempt to investigate the effects of age on the performance of a SVF test analyzing 5-s phases within a 30-s period. 2 The present study is noteworthy, because it is the first attempt to investigate the effects of age on the performance of a SVF test analyzing 5-s phases within a 30-s period.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Inconsistencies may possibly attributable to different age ranges and education levels of participants in different studies, since age and education has been shown to affect verbal fluency performance (Troyer et al, 1997; Tombaugh et al, 1999; Troyer, 2000; Brucki and Rocha, 2004; Lanting et al, 2009; Sauzéon et al, 2010). …”
Section: Introductionmentioning
confidence: 99%